The relationship between stride mechanics and shoulder distraction force in collegiate softball pitchers - Oliver, G. D.; Bordelon, N. M.; Yanagita, Y. (ISBS Proceedings Archive (Michigan), 2023)
The purpose of this study was to determine the relationship between stride mechanics and shoulder distraction force in softball pitchers. Sixty-three collegiate softball pitchers (age: 20.1 ± 1.3 yrs, height: 173.3 ± 7.4 cm, weight: 79.7 ± 11.7 kg) participated and threw three maximal effort fastballs for a strike. Kinematic data were collected using an electromagnetic tracking system with a sampling frequency of 100 Hz. Regression analysis revealed a significant positive relationship between stride length and shoulder distraction force [R2 = .11; F (1, 61) = 7.345, p = .009], where stride length accounted for 11% of the variation in shoulder distraction force. Specifically, shoulder distraction force increased by .94 N/kg for every 10% increase in stride length normalized as a percentage of body height.